Factors related to academic grades as a proxy for educational achievement - Ianina Tuñón; Santiago Poy (Universidad Autónoma de Baja California, 2016)
After eleven years of the Argentine government implementing different educational engagement policies, it is appropriate to look into the achievements in education. What sociodemographic, socioeconomic and sociocultural factors are linked to academic grades as a proxy for educational achievement in subjects such as Mathematics and Language in primary and secondary education? This study shows relatively well-known inequalities relating to sex and educational paths. Nevertheless, other influential sociocultural factors were explored which are relatively independent from socioeconomic and school administration factors, such as having books at home, reading behavior and storytelling. Moreover, the relationship between social stratification and the type of school management was identified. In order to achieve this, analyses were performed using logistic regression models based on microdata from the Argentine Social Debt Survey for 2011.